Potential CO2 removal from enhanced weathering by ecosystem responses to powdered rock - Goll, Daniel S.; Ciais, Philippe; Amann, Thorben; Buermann, Wolfgang; Chang, Jinfeng; Eker, Sibel; Hartmann, Jens; Janssens, Ivan; Li, Wei; Obersteiner, Michael; Penuelas, Josep; Tanaka, Katsumasa; et al. (Nature geoscience, 2021)
Negative emission technologies underpin socioeconomic scenarios consistent with the Paris Agreement. Afforestation and bioenergy coupled with carbon dioxide (CO 2 ) capture and storage are the main land negative emission technologies proposed, but the range of nature-based solutions is wider. Here we explore soil amendment with powdered basalt in natural ecosystems. Basalt is an abundant rock resource, which reacts with CO 2 and removes it from the atmosphere. Besides, basalt improves soil fertility and thereby potentially enhances ecosystem carbon storage, rendering a global CO 2 removal of basalt substantially larger than previously suggested. As this is a fully developed technology that can be co-deployed in existing land systems, it is suited for rapid upscaling. Achieving sufficiently high net CO 2 removal will require upscaling of basalt mining, deploying systems in remote areas with a low carbon footprint and using energy from low-carbon sources. We argue that basalt soil amendment should be considered a prominent option when assessing land management options for mitigating climate change, but yet unknown side-effects, as well as limited data on field-scale deployment, need to be addressed first. The enhanced CO 2 uptake by vegetation in response to powdered rock should be considered in assessing the feasibility of enhanced weathering as a negative emission technology in mitigating climate change, suggest simulations of a land surface model.